Evaluation of internal audit activity effectiveness in risk assessment of anti-money laundering area: a case of “Latvian Bank N" - Saksonova, Svetlana; Matvejeva, Arina (University of Latvia, 2019)
Due to recent AML violation cases occurred in financial institutions within Baltic States (Estonian Danske Bank, ABLV Bank AS and Versobank AS) and expressed concerns on Banks’ Internal Audit activity within AML area, the author sees the necessity for assessment of Internal Audit activity within AML area in order to determine the level of adequacy of AML regulatory changes within the risk assessment and potential gaps in risk assessment of AML area. The research focuses on AML compliance with the constantly evolving and increasingly more complicated regulatory requirements and evaluation of organizational part of IA activity using an example of a Latvian Bank N. The aim of this research is to investigate completeness of Internal Audit risk assessment in accordance with recent AML regulatory changes. This research also compares the IA organizational process that affects all banking areas between a Latvian Bank N and an Estonian practice. This research relies on qualitative methods. Qualitative methods include face-to-face interviews with Board Members of Latvian Bank N, AML Internal Auditor of Latvian Bank N and telephone interviews with Estonian IA Experts. Also, involves documentary analysis of Latvian Bank N internal audit risk assessment conducted in 2017 for the implementation in 2018. The conducted investigation showed that IA activity has certain deficiencies and shortcomings in relation to AML regulatory changes reflection in IA risk assessment for AML area, and for overall IA organizational process organization that is crucial for audits organization and conduction not only in AML area, but for all Latvian Bank N and other Latvian Banks’ activities areas. Elimination of these deficiencies will help to achieve full reflection of AML regulatory changes and thereby mitigate the risks that bank processes which are affected by these regulation changes are not sufficiently assessed within the Internal Audit Risk Assessment. In addition, elimination of the deficiencies identified in relation to IA organizational processes will lead to increase of conformance in accordance with International Standards for the Professional Practice of Internal Auditing (pub. the Institute of Internal Auditors, 2017) and, as a result, will strengthen and improve the IA activity effectiveness that is within Internal Audit department and Bank’s interest. Many of these results are likely to apply not only in the particular bank on which the research is focused, but also to other banks in Latvia. Thus, the research has practical implications in formulating common risk management tactics and methods that could be applied across the banking sector.